2022
DOI: 10.1152/jn.00003.2022
|View full text |Cite
|
Sign up to set email alerts
|

Even well-practiced movements benefit from repetition

Abstract: Professional golf players spend years practicing, but will still perform one or two practice swings without a ball before executing the actual swing. Why do they do this? In this study we tested the hypothesis that repeating a well-practiced movement leads to a reduction of movement variability. To operationalize this hypothesis, participants were tested in a center-out reaching task with four different targets, on four different days. To probe the effect of repetition they performed random sequences from one … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although the relationship between MV and performance depends on the nature of the intrinsic dynamics of the system and the constraints of the task ( Newell and Vaillancourt, 2001 ), the results obtained in the present study could be related to the players’ expertise level. Evidence shows that expert athletes tend to be more regular in their movements than novices ( Davids et al, 2008 ; Bashford et al, 2022 ), and furthermore, the practice of a movement or motor skill tends to reduce its MV ( Fernández-Valdés et al, 2020 ; Sutter et al, 2022 ), which can be used as an indicator of sport expertise. In this sense, it could be expected that the group of high-level female football players included in the present study, belonging to the first and second teams, would show differences in MV and passing accuracy when comparing both teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between MV and performance depends on the nature of the intrinsic dynamics of the system and the constraints of the task ( Newell and Vaillancourt, 2001 ), the results obtained in the present study could be related to the players’ expertise level. Evidence shows that expert athletes tend to be more regular in their movements than novices ( Davids et al, 2008 ; Bashford et al, 2022 ), and furthermore, the practice of a movement or motor skill tends to reduce its MV ( Fernández-Valdés et al, 2020 ; Sutter et al, 2022 ), which can be used as an indicator of sport expertise. In this sense, it could be expected that the group of high-level female football players included in the present study, belonging to the first and second teams, would show differences in MV and passing accuracy when comparing both teams.…”
Section: Discussionmentioning
confidence: 99%
“…(3) A third group with a low level of accuracy and high MV: For these players, the task would be excessively challenging, as they not only failed to achieve the task objective successfully but also did not reach a high level of control and regularity of movement. In this case, it would be appropriate to continue training to improve performance and decrease MV, although in certain players it may be necessary to decrease the difficulty or complexity of the task ( Fernández-Valdés et al, 2020 ; Sutter et al, 2022 ). Finally, (4) a fourth group with a low level of accuracy and low MV: These players would not have mastered the task to achieve their goal successfully and performed it with very regular and rigid movement, which is sometimes associated with a pathological situation or a history of injury ( Stergiou and Decker, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this principle—the updating of success probabilities—will naturally result in a system that shows hysteresis. Indeed, previous work has shown that hand choice is biased by recent successes when the probability of success is surreptitiously manipulated [ 22 ], and endpoint variability of reaches are lower when movements are made to the same target consecutively compared to movements to a new target [ 23 ].…”
Section: Introductionmentioning
confidence: 99%